Associations of MTHFR gene polymorphism with lipid metabolism and risk of cerebral infarction in the Northwest Han Chinese population - Guan, Dong; Ji, Yichun; Lu, Xiaoyun; Feng, Weiyi; Ma, Wenbing (Frontiers in Neurology, 2023)
Objective Genetic variation in the methylenetetrahydrofolate reductase (MTHFR) gene may contribute to the development of cerebral infarction (CI); however, results have been inconsistent across studies with different populations, including studies of the Chinese population. The aim of this study was to analyze the effect of MTHFR gene polymorphism on serum lipid and homocysteine levels among patients with CI in the Northwest Chinese Han population. Patients and methods A total of 521 CI patients and 524 non-CI controls were enrolled in the study. Polymerase chain reaction and hybridization were utilized to identify MTHFR gene polymorphisms. Multivariate logistic regression analysis was used to assess the associations of MTHFR gene polymorphism with risk of CI. Results Frequencies of the TT genotype and the T allele were markedly higher among CI patients than among controls. After stratifying our data by sex and age, we determined that these differences in frequency of the TT genotype and the T allele were statistically significant among participants of two different age brackets and among men, but not among women (i.e., there were no statistically significant differences between female patients and female controls). CI patients and control participants with the CT or TT genotype had significantly higher homocysteine (Hcy) levels than those with the CC genotype. Among CI patients, CT/TT carriers showed significantly lower high-density lipoprotein cholesterol (HDL-C) and apolipoprotein A-I (ApoA-I) levels as compared with CC carriers, but there was no significant difference for control participants. Multivariable logistic regression analysis showed that drinking; smoking; diabetes mellitus; levels of Hcy, direct bilirubin (DB), indirect bilirubin (IB), ApoA-I, and total protein (TP); and TT genotype were significant independent risk factors for CI. Conclusions The results suggested that the TT genotype of the MTHFR C677T gene polymorphism, which is associated with hyperhomocysteinemia (HHcy), might be of great clinical significance in the identification of new biomarkers for CI and in the development of individualized preventive and therapeutic strategies.